Redescription of Triatoma melanica Neiva & Lent, 1941, new status (Hemiptera: Reduviidae: Triatominae) - Costa, Jane; Argolo, Ana Maria; Felix, Márcio (Zootaxa, 2006)
Triatoma brasiliensis melanica Neiva and Lent is elevated to species status based on comparison of its morphology, biology, ecology, crossing experiments, allozymes, and mtDNA sequences with those of other members of the T. brasiliensis species complex. The taxon is redescribed from specimens from northern Minas Gerais State, Brazil.